Psychometric analysis of the PSUKS - polish version of the Revised Leadership Scale for Sport - Szulawski, Michał; Tokarski, Stanisław (Studia Psychologica: Theoria et praxis, 2007)
One of the numerous roles of the Psychology in Sport is to get to know the relationship between the sportsmen and their coach. The scale which allows to study this relation is the Revised Leadership Scale for Sport. Poprawiona Skala Umiejétnosci Kierowania w Sporcie (PSUKS) is the cultural adaptation of the above mentioned scale. The adaptation was the main purpose of my master thesis. The equivalence of PSUKS was checked in the areas of translation, reliability and validity. The translation of the scale was checked according to the back translation procedure. The reliability was measured with alpha Crombach coefficient. Most of the results show that the subscales of the PSUKS are reliable. Validity was checked with Factor Analysis. The Factor structure of the PSUKS is not exactly the same as the structure of the RLSS, but it is similar to some extend. The further research over the questionnaire are advisable and the current scale can be used as the experimental version, with the limited trust to the results.